Association of Antibiotic Resistance Traits in Uropathogenic Escherichia coli (UPEC) Isolates. (16th March 2022) - Rahman, Md. Mostafizer; Hossain, Mridha Md. Kamal; Rubaya, Rubaya; Halder, Joyanta; Karim, Md. Ekramul; Bhuiya, Anjuman Ara; Khatun, Anwara; Alam, Jahangir
Abstract : Background . Antimicrobial resistance (AMR) is a global health problem which is constantly evolving and varies spatially and temporally. Resistance to a particular antibiotic may serve as a selection and coselection marker for the same or different antibiotic classes. Therefore, this cross-sectional study was conducted to predict the association of phenotypic and genotypic resistance traits in uropathogenic Escherichia coli (UPEC). Method . A total of 42 UPEC from 83 urine samples were investigated for the prevalence and association of phenotypic and genotypic AMR traits. Antibiogram profiling was carried out by Kirby–Bauer's disc diffusion method and AMR genes (ARGs) were detected by PCR. Result . UPECs were isolated from 50.60% (42/83) of the samples examined. Of these, 80.95% of cases were derived from females, and 38.10% of cases were found in the age group of 21–30 years. The isolates were shown to have a high frequency of resistance to tetracycline (92.86%), followed by sulfonamide (71.43%), ampicillin (52.38%), trimethoprim-sulfamethoxazole (47.62%), and 28.57% each to streptomycin, chloramphenicol, and erythromycin. The most prevalent antimicrobial resistance genes (ARGs) in these isolates were tet (A) (78.57%), tet (B) (76.19%), sul 1 (61.91%), dfr A1 (35.71%), bla SHV (26.19%), cml A (19.05%), and CITM, qnrA, and cat A1 each at 11.91%. According to statistical analysis, ampicillin, sulfonamide, trimethoprim-sulfamethoxazole, and ciprofloxacin resistance were strongly correlated with the presence of bla SHV, sul 1, dfr A1, and qnr A, respectively. Nonsignificant associations were observed between ciprofloxacin-tetracycline, sulfonamide-erythromycin pairs as well as between tet (A) and tet (B) genes . Besides, coselection was also assumed in the case of chloramphenicol resistance genes, namely, cat A1 and cml A. Conclusion . Both the phenotypic and genetic resistance traits were found in the UPEC isolates. Statistical association and coselection phenomena among AMR phenotypes and genotypes were also observed but required to be validated in a broad-scale study. However, these findings might have important implications for the development of an AMR prediction model to tackle future AMR outbreaks.